Pengaruh Sistem Akuntansi Pemerintahan, Budaya Organisasi, Kinerja Aparatur Pemerintah Daerah, Peran APIP, Dan Sistem Pengendalian Intern Pemerintah Terhadap Penerapan Good Governance (Studi Empiris Di Kabupaten Kepulauan Talaud) - Mailoor, Jefri Herbert; Sondakh, Jullie J; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2017)
Abstract. This study aims to test empirically the effects of government accounting system, organizational culture, performance of regional government officials, the role of government internal auditor, and government internal control system towards the implementation of good governance in Talaud Islands District. This research was conducted at Talaud Islands Regency officials by using purposive sampling method. Data were collected by distributing questionnaires to 145 respondents at 28 SKPD. Data was analysed by using multiple linear regression with SPSS version 23 software. T-test was conducted to test the hypothesis partially. Results of this study show that: (1) The government’s accounting system has a positive and significant influence on the implementation of good governance, with t-value of 4.342 and significance value of 0.000; (2) The organizational culture has a negative and insignificant influence on the implementation of good governance, with t-value of -1.019 and significance value of 0.310; (3) The performance of regional government officials has a positive and significant influence on the implementation of good governance, with t-value of 2.458 and significance value of 0.015; (4) The role of APIP has a positive and significant influence on the application of good governance, with t-value of 6.647 and significance value of 0.000; (5) The government’s internal control system has a positive and significant influence on the implementation of good governance, with t-value of 2.128 and significance value of 0.035.  The amount of variation of the variables of good governance implementation which can be explained by variables in this research is 84.8%, while the remaining 15.2% is the contribution of other variables that are excluded in this research model. Keywords: Government Accounting System, Organizational Culture, Performance of Government Officials, The Role of Government Internal Auditor, Government Internal Control System, Good Governance.Abstrak. Penelitian ini bertujuan untuk menguji secara empiris pengaruh sistem akuntansi pemerintahan, budaya organisasi, kinerja aparatur pemerintah daerah, peran aparat pengawasan intern pemerintah, dan sistem pengendalian intern pemerintah terhadap penerapan good governance di Kabupaten Kepulauan Talaud. Penelitian ini dilakukan pada aparatur Kabupaten Kepulauan Talaud dengan menggunakan metode purposive sampling. Pengumpulan data dilakukan dengan menyebarkan angket kuesioner pada 145 responden di 28 SKPD. Metode analisis data menggunakan regresi linear berganda dengan bantuan SPSS versi 23. Untuk menguji hipotesis secara parsial digunakan Uji-t. Hasil penelitian menunjukkan bahwa: (1) Sistem akuntansi pemerintahan berpengaruh positif dan signifikan terhadap penerapan good governance, dimana nilai t= 4,342 dan nilai signifikan 0,000; (2) Budaya organisasi berpengaruh negatif dan tidak signifikan terhadap penerapan good governance, dimana nilai t= -1,019 dan nilai signifikan 0,310; (3) Kinerja aparatur pemerintah daerah berpengaruh positif dan signifikan terhadap penerapan good governance, dimana nilai t= 2,458 dan nilai signifikan 0,015; (4) Peran APIP berpengaruh positif dan signifikan terhadap penerapan good governance, dimana nilai t= 6,647 dan nilai signifikan 0,000; (5) Sistem pengendalian intern pemerintah berpengaruh positif dan signifikan terhadap penerapan good governance, dimana nilai t= 2,128 dan nilai signifikan 0,035. Besarnya variasi dari variabel penerapan good governance yang dapat dijelaskan oleh variabel-variebel penelitian ini adalah sebesar 84,8 %, sedangkan sisanya sebesar 15,2 % dijelaskan atau merupakan kontribusi variabel lain tetapi tidak terdapat dalam model penelitian ini. Kata Kunci:   Sistem Akuntansi Pemerintahan, Budaya Organisasi, Kinerja Aparatur Pemerintah, Peran Aparat Pengawasan Intern Pemerintah, Sistem Pengendalian Intern Pemerintah, Good Governance.